Effects of Four Foundations of Mindfulness-Based Intervention (FFMBI) on Salivary Cortisol Levels, Body Composition, Blood Pressure and Pulse Rate, and Brain Waves of Practitioners - Nadnapang Phophichit; Phramaha Phuen Kittisobhano; Phramaha Anon Anando; Phramaha Duangthip Pariyattidhari; Sakchai Sakabucha; Wilasinee Jeungprasopsuk; Tararat Khaokhiew (Spirituality Studies)
This study examines the effects of the Four Foundations of Mindfulness-Based Intervention (FFMBI) on various physiological and psychological markers, including salivary cortisol, body composition, blood pressure, pulse rate, and brain waves. Using a mixed-methods approach, in-depth interviews with 12 Vipassana meditation masters and Buddhist scholars were conducted to develop the FFMBI program. A quantitative experimental study with 30 volunteers participating in a 7-day meditation retreat assessed changes in physical and mental states. Results showed a significant reduction in self-reported stress scores (from 32.07 to 23.00, as measured by the SPST-20) and improvements in brainwave alpha/beta ratios (highest scores increased from 54.84 to 79.82, and average scores increased from 6.16 to 9.80), indicating enhanced mental relaxation. Body weight slightly decreased, and BMI and obesity levels improved, though heart rate and blood pressure showed no significant changes. Unexpectedly, salivary cortisol levels increased, indicating a need for further investigation into the physiological responses to FFMBI. Overall, the findings highlight the positive impacts of FFMBI on both physical and mental well-being.